Pengaruh Beban Kerja, Stres Kerja Dan Kepuasan Kerja Terhadap Kinerja Karyawan Kantor BPJS Kesehatan Cabang Magelang - Novita Widiastuti; Nur Wening (Jurnal Manajemen Kreatif dan Inovasi, 2024)
In order to achieve effective and efficient organizational goals, it is necessary to improve employee performance at BPJS Health Magelang Branch. Suitability of workload for each employee is an important factor in creating good conditions for each employee. Apart from that, the condition of employees with low stress and high satisfaction with the organization is a key variable in realizing increased employee performance. This research aims to determine the influence of these three variables on employee performance. The method and analysis used in the research is a quantitative method with multiple regression analysis. The data collection technique used was a questionnaire to all permanent employees at BPJS Health Magelang Branch with a total of 48 respondents. The results of this research show that first, there is a significant and negative influence of workload on employee performance as evidenced by the calculated t value of -3.096 and a significance of 0.003. Second, work stress has a significant and negative influence on employee performance as evidenced by the calculated t value of -2.642 and a significance of 0.011. Third, job satisfaction also has a significant and positive influence on employee performance as evidenced by the calculated t value of 2.641 and a significance of 0.018. Fourth, from the results of calculating the coefficient of determination it can be concluded that workload, work stress and job satisfaction together have an influence on employee performance was 56.5%.